Can heritage bring peace and prosperity? - Babić, Darko (Array, 2006)
What is heritage? Where does it exist? What is knowledge versus wisdom, and why is it important? The foundation of heritage lies within ‘ elements of heritage’ , those pretty big amounts of tangible (objects, monuments, sites...) as well as intangible (customs, languages, music...) ingredients which are still predominately defined as ‘ heritage’ . But heritage is far beyond that. Considering that on the lower level (i.e. knowledge level) the collective memory exists, and heritage occupies the upper level (wisdom level) since heritage is selected and carefully filtered collective memory necessary for right judgments. In other words, heritage is wisdom and it becomes that only by meaningful use of collective memory, by use for the benefit of common good. With that “ spiritus movens” the heritage could become the real vehicle of human prosperity. The theoretical approach is examined with three case studies from Croatia.